Enhancement of latent fingerprint using dyed eggshell powder / Kavitha Rajagopal - Rajagopal, Kavitha (2021)
History has told that Chinese used the fingerprint to sign legal documents far back to three thousand years ago. An Englishman named Francis Galton has conducted an extensive research regarding fingerprint. Most importantly, he concluded that no two fingerprints are the same and the pattern remained unchanged throughout individual's life. Mainly, it is divided into two which are visible and latent fingerprint. Obviously, locating the latent fingerprint is much more difficult and requires the use of technique to make the print visible. One of the most common way to locate fingerprint in non-porous surface is fingerprint powder. Experienced examiners find that grey and black powders are adequate for most latent-print work. The examiner will select the powder which afford the best color contrast with a surface being dust. In addition, there are other types of powders are available for developing the latent prints. These include magnetic powder and fluorescent powder. However, an innovation or invention is highly valuable in science and others field. Therefore, the idea of using waste material to enhance the latent prints is studied. Eggshell is a solid waste, with production of several tons per day. Eggshell is mostly sent to the landfill with a high management cost. It is economical to transform the eggshell waste to create new values from these waste materials. Current potential of eggshell are biodiesel, absorbent, biomaterial and fertilizer. Therefore, it is highly beneficial to explore the use of this common household waste product into a material to be used in criminalistics.